COVID-19 Impacts on Water Burden among Households in Turkana - Ong'ech, D; Olago, D; Dulo, S; Opondo, M; Ouma, G; Mumma, A; Hope, R; Charles, K (Office of DVC Research, Innovation and Enterprise, University of Nairobi, 2021)
This policy brief highlights findings from a study assessing respondents’ views on the impact of the pandemic on water security and its burden on households in Turkana County, Kenya. It also established possible solutions to the risks faced by communities in Turkana. The REACH Programme implemented a household survey of 909 household heads in Turkana Central in October 2017.